Landscape gardener Ogawa Jihei and his times a profile of modern Japan - Suzuki, Hiroyuki 1945-2014 (Japan Publishing Industry Foundation for Culture, 2018)
Securing the generous support of the politicians and industrialists who propelled Japan's modernization, Ogawa Jihei VII created many outstanding gardens at the end of the nineteenth and the first few decades of the twentieth century. expressing a Japanese aesthetic even while incorporating modern techniques, his methodology reveals the nature of modernization as Japan experienced it. With a keen eye for architecture, the author takes a long-awaited look at modernization and the modern garden
"Originally published in Japanese under the title 'Niwashi Ogawa Jihei to sono jidai' by the University of Tokyo Press in 2013"--title page verso. - Impressum auch in Japanisch
Keywords: Ogawa, Jihē -- VII -- 1860-1933; Gartenkunst; Japan; Ogawa, Jihē / 1860-1933; Gardens / Japan / History / 19th century; Gardens / Japan / History / 20th century